Legal Uncertainty Of Foreign Share Ownership In The Construction Services Sector - Yogaswara, Aisyah Jasmine (JURNAL USM LAW REVIEW, 2023)
This article is written to analyze the legal uncertainties found in the positive regulation related to the foreign ownership limitation in the construction services sector. In 2020, the Indonesian government issued the Job Creation Law which changed several laws and regulations including the Investment Law. According to the amended Investment Law, provisions regarding investment requirements are further regulated in a Presidential Regulation, in this case Perpres 10/2021 and Perpres 49/2021. However, both regulations do not stipulate any foreign ownership limitation in the construction services sector and the foreign ownership limitation regulated under other regulations instead. The most suitable method for this research is the normative juridical method, which is therefore used in this article. Until the writing of this article, there has been no research that examines the same subject matter, so the authors assess the importance of conducting this research. After this research was performed, it was found that legal uncertainty regarding restrictions on foreign shares in the construction services sector was found in the appendix of PP 5/2021 with the foreign ownership limitation for ASEAN BUJKA of 70% and Non-ASEAN BUJKA of 67%.